Analisis Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran PAI Di SMA Muhammadiyah Kota Bima - Mayada Mayada; Luthfiyah Luthfiyah; Nasaruddin Nasaruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze students’ activeness in Islamic Religious Education (PAI) learning at SMA Muhammadiyah Bima City using the Problem-Based Learning (PBL) model. The main focus is to obtain in-depth information regarding the level of students’ activeness in the implementation of the Problem-Based Learning (PBL) model. The research method used is qualitative with a descriptive-analytical approach. Qualitative research emphasizes the quality and meaning behind phenomena to describe the experiences of individuals or groups through documentation and personal analysis. The results of the study indicate a significant increase in students’ activeness after the implementation of the Problem-Based Learning (PBL) model. This is reflected in improved cooperation and group cohesion, the increased frequency of students expressing opinions and providing feedback, and their ability to complete tasks assigned by the teacher effectively. In addition, students become more courageous and confident when asking and answering questions. They are no longer hesitant to express their opinions or to provide responses to their peers during presentations. Based on the analysis and discussion, it can be concluded that the Problem-Based Learning (PBL) model can enhance students’ learning activities. This is evident from the improvement in students’ collaborative processes in identifying, formulating, and solving problems in groups, as well as their increased participation in giving opinions and successfully completing assigned tasks.